Water circulation pattern in the coastal waters of Port Dickson, Malaysia. - Saadon, M. N.; Liew, Hee Chong
The study was conducted In front of the UPM Station in Port Dickson between 21st August to 25th August 1988. Two methods were used In- this study, i.e. the Lagrangian and Eulerian methods.